THE REACTION CAUSED BY WORK STRESS, JOB SATISFACTION, AND ORGANIZATIONAL COMMITMENT TO TURNOVER INTENTION ON THE EMPLOYEES AT PT. BALI TOWERINDO SENTRA, TBK - Abednego, Abednego; Bohlen Purba, Charles (Dinasti Publisher, 2021)
This research aimed to investigate the affect which appeared on Employees at PT. Bali Towerindo Sentra Tbk relates to the high of turnover intention which caused by work stress, job satisfaction and organizational commitment. This research was included in type of causality research with quantitative research methods. Those population here was employees at PT. Bali Towerindo Sentra Tbk, which amounted to 395 people. Meanwhile, the sample consisted of 202 respondents (Slovin, 5% error tolerance). Data analysis method that used was multiple linear regression analysis to examine all the research hypothesis. The outcomes earned from this research was illustrated that work stress, job satisfaction and organizational commitment had a positive and significant impact on turnover intention. Work stress, job satisfaction and organizational commitment were also had simultaneously impact towards the turnover intention.